A study on the utilization, perception and potential of social media as a marketing tool: the case of travel agencies in Azerbaijan - Babak, Aghalarov (2014)
In the last years Internet and Social Media has influenced business-to-customer and customer-to-customer relationships. Concurrently, this influence is still growing and businesses are paying more and more attention to these new marketing tools in their overall marketing strategy. Although there are already some studies that investigate Social Media Marketing, most of these studies have examined Social Media use and perceptions from consumers? perspective. In academic literature there is lack of studies about Social Media from business context and little guidance on how to use Social Media in an effective way for travel companies. Therefore considering aforementioned gap this study aims to analyze Social Media as a marketing tool in the tourism business context from the practitioners? perspective and provide guidelines for travel agencies in Baku, Azerbaijan. In order to achieve this aim the following objectives have been defined: to understand how Social Media are being approached in the literature as a marketing tool, in particular in the tourism industry, to investigate the perception of travel agencies regarding Social Media as a marketing tool, to analyze the current usage and maintenance of Social Media by travel agencies, to identify the major problems of travel agencies regarding Social Media usage and to identify and recommend effective ways of using Social Media by travel agencies. These objectives were achieved using two main methods. The first semi-structured interviews were used to collect data from a selective sample of six travel agencies in Baku, Azerbaijan through the periods of April, May and November. The second method was used to complement the data from interviews with analyzing their Social Media presence and activity, namely on their Facebook pages during the month of November.According to the results of the study, Social Media is not fully exploited as a marketing tool and is used just another channel for advertising. Moreover, the participants have a lack of regular activity at their Social Media channels. Social networking sites (Facebook) are ii mostly used by participants and they are perceived as the most effective channels. The overall uptake of other Social Media channels is in early stage and they are not considered powerful as a marketing tool by participants. There is no clear target market and marketing strategy defined for Social Media usage by travel agencies. The study also revealed that perceived difficulties for the usage of Social Media by travel agencies are lack of time, lack of knowledge and difficulty to measure the success of Social Media. Moreover, the analysis of the collected data revealed several problems regarding the usage and adoption of Social Media as a marketing tool by travel agencies in Baku, Azerbaijan. After identifying the problems, set of recommendations that is intended to assist the effective adoption and usage of Social Media for travel agencies are provided.